Analisa Sifat Mekanis Komposit Epoksi/Partikel Silika dari Ekstraksi Sekam Padi: Bagian II: Pemodelan - Mulyadi, Mulyadi (CV. IRA PUBLISHING, 2022)
The influence of silica (silicon dioxide) on mechanical properties of modified epoxy resin were studied using computer modelling. Particulate composite was made of Eposchon resin system and modified with 0, 2, 4 and 5% of silica by weight. Salome Meca open source software is applied to model three point bend test. The results were validated by means of experimental outcomes. It was shown that that bending strength of modified epoxy resin was improved by 14% for the maximum with 4% of silica content. On the other hand, fracture toughness were decreased as silica particles introduce into the epoxy system. Furthermore, fracture toughness enhanced as the content of silica higher up to 5%. It is concluded that silica from rice husk is a potential filler for polymer composite materials.